The paradox of China's tobacco industry: competition through monopoly policy. (19th May 2021) - Liao, Allen; Cole, Benjamin
Abstract: This study documents the evolution of China's tobacco industry over 70 years from that of unordered local trade to ordered competitive national industry. We develop a theoretical framework regarding three levers the central government utilized—quota pliability, price tiering, and public rankings—to shift the attention of producers from merely fulfilling quotas to seeking quota partners, building scale economies, and developing high quality brands. The findings provide insights to those interested in planned economies, industry dynamics, and China's industrial development.